Textbook on the code of criminal procedure - Gaur, K D (Gurgaon Universal, 2020)
Textbook on the Code of Criminal Procedure written by Professor K D Gaur, an eminent jurist of international repute is a classic on Code of Criminal Procedure, 1973 (2 af 1974). The book has been written to fulfill long felt need of an authoritative text on the subject for students, teachers, members of the Bar and Bench, prosecutors, defence personnel, police officials and those interested in the administration of Criminal Justice.
Keywords: Criminal Law